Anticipatory grief in caregivers of elderly people with advanced Alzheimer's disease - Vanderley da Rocha, Danielly (2023)
Objective: to understand how anticipatory grief is experienced by caregivers of elderly people with advanced Alzheimer's disease. Methods: this is a field, cross-sectional and qualitative research. A sociodemographic questionnaire and a semi-structured interview were applied. The data were treated from the content analysis. Results: the participants were four caregivers. Three categories were elaborated: Feelings on the experience of anticipatory grief in care; Relationships and strategies in the care process; and Impacts of the professional routine on the caregiver's quality of life. Family interference was pointed out as negative in the manifestation of elderly people’s autonomy, impairing the care routine. It was also observed that the absence of regulation caregiver as a profession implies work overload, limited care strategies for elderly people with AD, lack of delimitation of action and negligence of self-care. Conclusion: the severe loss of autonomy and functionality of the elderly awakens feelings of sadness and distress in the caregivers, and it also brings them closer to the awareness of the other's death and their own finitude.